Peran Mediasi Literasi Keuangan Syariah terhadap Kinerja Keuangan UMKM: Perspektif Kompetensi, Fintech, dan Pengendalian Internal - Mohammad Ridwan; Sukamto Sukamto; Sulistyo Suharto (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the influence of manager competence, financial technology, and internal control systems on MSME financial performance, both directly and indirectly through Sharia financial literacy as a mediating variable. This study uses a quantitative approach with an exploratory design. Primary data were obtained by distributing questionnaires to 400 MSMEs in Semarang City selected using a purposive sampling technique. Data analysis was conducted using SEM-PLS. The results show that manager competence and financial technology have a positive and significant influence on MSME financial performance, while internal control systems do not have a significant direct influence. Manager competence, financial technology, and internal control systems are proven to have a positive and significant influence on Islamic financial literacy. Furthermore, Sharia financial literacy has a positive and significant influence on MSME financial performance and is able to mediate the influence of manager competence, financial technology, and internal control systems on MSME financial performance. These findings confirm that Sharia financial literacy is a strategic capability that plays a role in transforming an organization's internal resources into improved financial performance. This research contributes to the development of the Resource-Based View and Dynamic Capability theories and offers a model for improving the financial performance of MSMEs based on Islamic financial literacy.